Identifying Chamaecrista rotundifolia accessions and Centrosema species for bridging seasonal feed gaps in smallholder mixed farms in the West African derived savanna - Larbi, Asamoah; Adekunle, I.O.; Awojide, A.A.; Akinlade, J. (1999)
Information is scanty on seasonal changes in the yield and quality of forage legumes adapted to the West African savannas. Two experiments were conducted from 1992-1994 in the derived savanna zone of West Africa to determine the dry matter (DM) yield and 48-h in sacco DM digestibility of 17 accessions of Chamaecrista rotundifolia (Experiment 1), and 22 accessions of 8 Centrosema species (Experiment 2) in the main-wet (April-August), minor-wet (September-November), and dry (December-March) seasons. Accessions varied significantly in DM yield and in Sacco DM digestibility in both experiments. Based on the digestible DM yield, accessions were identified with the potential ot provide greater quantities of high quality forage. These included: Ch. rotundifolia ILCA 14165; Ce. acutifolium ILCA 12182 and 12184; Ce. macrocarpum ILCA 15594; Ce. pascuorum ILCA 9; Ce. schottii ILCA 122 and 12401; and Ce. plumieri ILCA 200; for the wet season. Promising accessions for the dry season included: Ch. rotundifolia ILCA 14172 and 14174; Ce. acutifolium ILCA 15591; Ce. arenarium ILCA 12451; Ce. brasilianum ILCA 155; Ce. macrocarpum ILCA 15594; Ce. plumieri ILCA 194; and Ce. schottii ILCA 122. Of the Ce. virginianum accessions evaluated, ILCA 509 was the best in all seasons. The potential of the promising accessions to reduce seasonal deficiencies of high quality feed, especially during the dry season, and their multiple use of soil fertility maintenance, weed control, and pest management in mixed farming systems warrant further research.